IFPRI Policy Seminar "Evidence-Based Policymaking" - Hoddinott, John (2011)
Presentation by John Hoddinott, senior research fellow at the International Food Policy Research Institute at the IFPRI Policy Seminar held on 2 June 2011 "Evidence-Based Policymaking: Challenges, Methods, and Innovations in Assessing Policy Influence".